Wedge reflection positivity - Casini, Horacio German (2011)
We show that there is a positivity property for Wightman functions which is analogous to the reflection positivity for the Euclidean ones. The role of Euclidean time reflections is played here by the wedge reflections which change the sign of the time and one of the spatial coordinates.